Asymmetric cell division: fly neuroblast meets worm zygote. - Doe, C.Q.; Bowerman, B. (Current Opinion in Cell Biology, 2001)
Both Drosophila neuroblasts and Caenorhabditis elegans zygotes use a conserved protein complex to establish cell polarity and regulate spindle orientation. Mammalian epithelia also use this complex to regulate apical/basal polarity. Recent results have allowed us to compare the mechanisms regulating asymmetric cell division in Drosophila neuroblasts and the C. elegans zygote.